TOWARDS WELL-BEING, THROUGH EDUCATION AND CULTURAL INTEGRATION - Sanda NICOLA (Association of Social and Educational Innovation, 2022)
The decision to emigrate is almost always preceded by a period of unhappiness, and those who leave their homeland rely on this major change to improve their well-being. The strategies used by immigrants to integrate socially in the host country differ depending on several factors, such as: age, education, marital status, religion, connection to pre-existing support networks between compatriots, language proficiency or their long-term projections. In this paper we deliver a case study revealing a new pattern of migration: exponents of the Romanian middle class who choose emigration in their mid-life considering that Brussels, more than any other potential destination, ensures favourable conditions to reach their well-being aspirations. The study is a qualitative research based on data obtained through semi-structured interviews and questionnaires, correlated with official quantitative data provided by Statbel, Eurostat, the European Commission, and the European Parliament on the migration of Romanians, particularly focusing on those with tertiary education. The findings of this research define the highly skilled Romanian immigrants in Brussels as a population that capitalizes on 1) European citizenship 2) tertiary achievement and 3) multilingualism, thus obtaining a transnational lifestyle and a stage of well-being that was still inaccessible in their country of origin, regardless of social status.